Professionalität und Professionalisierung von Lehrpersonen Perspektiven, theoretische Rahmungen und empirische Zugänge - Hinzke, Jan-Hendrik; Keller-Schneider, Manuela (Studien zur Professionsforschung und Lehrer:innenbildung, 2023)
The academic discourse on the "professionalism and professionalisation of teachers" has become more differentiated in recent years. Against this background, the volume provides an introductory insight into the plurality of professional theory approaches, the diversity of methodological approaches and the spectrum of researched content. This is followed by twelve empirical contributions on current research projects, which are arranged in the volume according to three main areas: "Professionalisation of student teachers in relation to the practical field of school", "Actors influencing the professionalisation of student teachers" and "Professionalisation and professionalism of teachers in the school field". The aim of the volume is to enrich the multifaceted discourse on professionalisation and professionalism based on studies, to enable a meta-perspective on the diversity of the discourse and to encourage reflection on this diversity.